Mechanisms of Helicobacter pylori Resistance to Antibiotics - Yahya Al-Jumaily, Asma; Sajid Al-jubori, Sawsan (Diyala Journal of Medicine, 2024)
Background: Helicobacter pylori is the most frequent human bacterial infection worldwide; it is prevalent in approximately half of the world's population. H.pylori poses a major health risk because it possesses distinct virulence factors and highly resistant to antibiotics. Multidrug resistance (MDR) and single-drug resistance are two distinct resistance profiles. Chromosome mutations influence antibiotic activity via target-mediated pathways. Inadequate drug absorption, efflux pumps activity, biofilm development, and cocci formation represent supplementary biological mechanisms by which H.pylori acquires drug resistance. The overexpression of efflux pumps genes in mutant isolates is readily detectable in post-therapy courses. Objective: Characterization of the biological and molecular mechanisms contributing to the development of antibiotic resistance in H.pylori. Conclusion: An alarming rate of drug-resistant H.pylori is on the rise. Primary and acquired resistance to clarithromycin and metronidazole has increased globally. Bacterial factors including biofilms, efflux pumps, and molecular mechanism are in association with H.pylori resistance. It is important to continue to monitor the resistance profiles of H.pylori isolates.